2011
DOI: 10.1155/2011/932973
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Melanoma of the Urinary Bladder

Abstract: Introduction. Primary melanoma of the urinary bladder is very rare. As far as we know, 19 cases have been reported worldwide, usually as case reports. Case Presentation. We present a 71-year-old male patient presented with a 2-month history of hematuria. Ultrasonography revealed a 5-cm-size mass located in the bladder trigone. A transurethral resection of the bladder tumor (TURBT) revealed a malignant melanoma. Evaluation for metastatic disease was negative. The patient deceased five months later before radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The function of melanocytes in mucosal membranes is still not known, but it cannot be protection from UV light. Mucosal tissue all over the body may be affected, except the ureters, where primary mucosal melanoma has never been reported .…”
mentioning
confidence: 99%
“…The function of melanocytes in mucosal membranes is still not known, but it cannot be protection from UV light. Mucosal tissue all over the body may be affected, except the ureters, where primary mucosal melanoma has never been reported .…”
mentioning
confidence: 99%
“…Transurethral resection of the lesion, partial cystectomy, radical cystectomy, chemotherapy, and radiation therapy had been used to treat melanoma of the urinary bladder. 6,11,12 It was stated by some authors that, in all patients with localised tumour, radical surgery seemed to be the therapy of choice, although to date none of the patients survived more than three years despite cystectomy characterizing the poor prognosis of the tumour. 13,14 TUR is a good option for treatment of small tumours, but always not adhering to the surgical principle of wide local excision.…”
Section: Discussionmentioning
confidence: 99%
“…El-Ammari et al [ 6 ] in 2011 reported a 71-year-old Moroccan male who presented with a 2-month history of gross haematuria. There was no past history of calculous disease or flank pain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The patient died five months later before any radical treatment could be performed. El-Ammari et al [ 6 ] stated that to their knowledge at the time of their publication in 2011 19 cases of primary melanoma of the urinary bladder had been reported worldwide in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation